THEORETICAL CHARACTERIZATION AND DESIGN OF EFFICIENT PHOTOACTIVE MATERIALS BASED ON ANTHRA[2,3-c]PYRROLE AND ANTHRA[2,3-c]THIOPHENE DERIVATIVES AIMED TOWARDS ORGANIC SOLAR CELLS - Cuadro Bautista, Walter (2017)
In this research we have designed electron donors D-π-A type containing two different π fragments to obtain anthrapyrrole (D-APR-A) and anthratiophene (D-ATF-A) derivatives, proposed for the use in organic bulk hetero-junction (BHJ) solar cells (OSCs). These derivatives were characterized by DFT and TD-DFT calculations. For all the electron donors the anchorage fragment was 2-methylenemalononitrile, while the chromophore fragment was spanned between diphenylamine, triphenylamine, thiophene. Estimation of the energy from HOMO and LUMO orbitals was discussed. Properties affecting open-circuit photovoltage (VOC) and short-circuit photocurrent (JSC) from D-π-A type derivatives were investigated, such as geometric structure, exciton driving force energy, energy gap and absorption spectra. Theoretical calculations from TD-DFT within Coulumb Attenuation Method CAM-B3LYP were able to predict excited state properties. The electron donors D-π-A type exhibit an estimated photoelectric conversion efficiency (PCE) above 10%. The anthrapyrrole derivatives along with the [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) are the complexes with higher photoelectric properties, being the Da-APR-A derivative the best projection with a PCE of 13,39%, therefore, these complexes are proposed as photoactive materials in the construction of organic bulk hetero-junction solar cells.